Mitigating Risks of Swallowed Button Batteries: New Strategies Before and After Removal. Issue 5 (May 2020) - Lerner, Diana G.; Brumbaugh, David; Lightdale, Jenifer R.; Jatana, Kris R.; Jacobs, Ian N.; Mamula, Petar
Abstract : ABSTRACT: Despite ongoing efforts of the national Button Battery Task Force (BBTF), cases of major morbidity and mortality continue to be reported at a higher rate after ingestion of higher voltage and larger button batteries. Initiation of sucralfate or honey shortly after some button battery ingestions is crucial to prevent further injury while awaiting emergent removal. Endoscopic acetic acid irrigation post removal of button battery may halt deeper injury. Gastroenterologists need to be aware of the updates to the National Capital Poison Center algorithm for button battery ingestion. Abstract : Supplemental Digital Content is available in the text